Fiscal transfers and public health services in China: a macro–micro analysis - Tu, Xunhua; Yan, Jie; Wang, Yueyi; Zheng, Jing (Frontiers in Public Health, 2025)
IntroductionThis study innovatively integrates functional performance and systemic capacity dimensions to establish a comprehensive evaluation framework for public health services, addressing critical knowledge gaps in fiscal policy-health system interactions.MethodsUtilizing multi-source spatial panel data from 1,871 Chinese counties (2001-2020), we developed a novel assessment system combining structural equation modeling (SEM) and fuzzy comprehensive evaluation. Complementary analyses of 283 prefecture-level cities employed fixed-effects models with instrumental variables to examine fiscal transfer mechanisms.ResultsOur findings reveal: Significant positive association between fiscal transfers and service levels. Dual-path mediation effects: Fiscal expenditure restructuring; Health spending efficiency optimization. Micro-level health equity improvements.DiscussionThese evidence-based results provide policymakers with actionable insights for: Establishing performance-oriented accountability frameworks; Promoting health equity through fiscal system optimization; The proposed multidimensional evaluation system offers a replicable toolkit for global health governance assessment.